Between bodies and collectivities: Articulating the action of emotion in obesity epidemic discourse - Fraser, Suzanne; Maher, J.; Wright, J. (Palgrave Macmillan Ltd., 2010)
Over the last decade intense concern has developed about what has been characterised as an obesity epidemic in the West. This concern has been accompanied by equally intense debates over the validity of this characterisation. Many critics see the epidemic designation as part of an intensifying 'moral panic' about fat in which emotions about fat shape the public and scientific debate. In this article we explore the critical literature on the obesity epidemic, noting the way in which it draws attention to the role of the emotions in discourse on the epidemic. We argue that the action of emotions in this context invites further theorisation, and that this theorisation needs to be undertaken via concepts that: (1) explicitly integrate the body and the emotions with the materialisation of political discourse, (2) avoid individualising and psychologising accounts of the emotions and (3) analyse the action of emotion in political debate without implying the need to eradicate emotion in generating more just and accurate perspectives. To this end, we turn to the work of Sara Ahmed, who has developed a sophisticated account of the role of the emotions in constructing social collectivities through their engagement with ideas of the body. We argue that this theory can be used to illuminate both the general relationship between public discourse and subjectivity, and the specific relationship between the self, the body and the oftentimes unmet imperative to slimness.